Acculturation process of migrant students in adult education : a case study of language acquisition in iltalukio, Finland - Akinola, Adeola (My University, 2019)
The research task focuses on how each cultural entity represented among the migrant students negotiate the seeming differences between their cultural and linguistic heritage and that of the host culture, Finland. Furthermore, the research attempts to frame the students’ strategy for language acquisition based on Berry’s acculturation model (1997) also referred to as acculturation process. The study was conducted during three terms at an English language course at Iltalukio (translated as afternoon/evening schools) in Southwest Finland for students who are not able to attend mainstream high schools due to age (adult students) and/or insufficient language skills in Finnish as the language of instruction. At the non-mainstream school, migrant students have the opportunity to continue/complete their studies while increasing their language proficiency; therefore these types of schools have the capacity to provide the last two years of comprehensive schooling (referred to as P7, P8) and its qualifications. The research is guided by these questions: (i) What type of language learning strategies are migrant students employing as part of their acculturation process? (ii) In what ways could migrant students’ language learning strategies be supported by teachers and school leadership within the classroom environment, and (iii) In what ways can teachers in multilingual and multicultural classrooms be supported? A qualitative methodology using observations, semi-structured interviews, one-to-one teaching, learning journal, audio recording and pictures, was designed to collect data. The data was analysed using thematic analysis (TA) to find recurring themes which may provide further insights. This research evolved from ongoing discourse about migrant students’ school burnouts, the seeming challenges/conflicts in (migrant)student-teacher relationships which stems from certain cultural and linguistic distance, and the various attempts by stakeholders (policy-makers, researchers, teachers, etc) to resolve these challenges.
Keywords: adult/continuous education in Finland, migrant youth, acculturation process, sociocultural learning theory, Culturally & Linguistically Responsive Teaching (CLRT), iltalukio